Design principles as a theoretical production of design-based research: contributions of dialectics to a methodology for teaching algorithms and computer programming. - Novais dos Santos, Gidevaldo; Nonato, Emanuel do Rosário Santos (EDeR. Educational Design Research, 2025)
A complex educational problem is the starting point for using DBR in education. In this research, the problem involved teaching algorithms in Computer Science based on collaborative learning and the use of a remote laboratory. The teaching and learning of algorithms is a relevant topic for research in education and computing, and we found the right research methodology in DBR. To conduct the research, the following question was defined: How can algorithms and programming be taught from the perspective of collaborative learning using a Remote Laboratory in a virtual learning environment? The aim was to develop a methodology for teaching algorithms and programming through collaborative learning using a remote laboratory in a virtual learning environment. DBR was used as a method, based epistemologically on dialectics, producing knowledge, and expanding the characteristics of the method, such as dialogue, interaction, and collaboration. Two procedures were used to produce the data: checklist and focus group. The prototype was evaluated in four iterations: two iterations with teachers and two with students, refining and changing the version. The focus group broadened the dialogue on the evaluation. The results showed that teachers and students perceived the relevance and consistency of the prototype in a similar way. This agreement indicated the soundness of the proposed solution. The results show the design principle, with a substantive and procedural emphasis, of collaborative learning as a methodological solution for teaching algorithms in a remote laboratory, in a dialectical pedagogy.